Evaluating natural variation, heritability, and genetic advance of photosynthetic traits in rice (Oryza sativa) - Acevedo-Siaca, Liana G.; Coe, Robert; Quick, W. Paul; Long, Stephen P. (Wiley, 2021)
Despite significant advances to harvest index and interception efficiency, photosynthesis has remained largely unimproved through conventional breeding approaches. However, increasing photosynthetic efficiency is a key method for enhancing crop productivity, yield, and sustainability. In this study, photosynthetic and morphological traits were characterized in indica rice to examine natural variation and the potential for hybridization in the future. Additionally, broad‐sense heritability (H2) was calculated for photosynthetic traits, including, for the first time, biochemical limitations to photosynthesis. Heritability was high for CO2 assimilation in saturating light and [CO2] (Amax; H2 = .65), the maximum rate of carboxylation (Vc,max; H2 = .63), the maximum rate of electron transport (Jmax; H2 = .68), and triosephosphate utilization (TPU; H2 = .73). Genetic advances of up to 17.7% were estimated, suggesting that it would be possible to not only select for the improvement of biochemical components of photosynthesis but also achieve significant gains in one generation. Heritability was low for CO2 assimilation at ambient [CO2] in saturating light (Asat; H2 = .22), suggesting that rising [CO2] may increase heritability for photosynthesis in rice.